The 2016 Academic Emergency Medicine Consensus Conference, "Shared Decision Making in the Emergency Department: Development of a Policy‐relevant Patient‐centered Research Agenda" Diagnostic Testing Breakout Session Report. (25th November 2016) - Barrett, Tyler W.; Rising, Kristin L.; Bellolio, M. Fernanda; Hall, M. Kennedy; Brody, Aaron; Dodd, Kenneth W.; Grieser, Mira; Levy, Phillip D.; Raja, Ali S.; Self, Wesley H.; Weingarten, Gail; Hess, Erik P.; et al.
Abstract: Diagnostic testing is an integral component of patient evaluation in the emergency department (ED). Emergency clinicians frequently use diagnostic testing to more confidently exclude "worst‐case" diagnoses rather than to determine the most likely etiology for a presenting complaint. Increased utilization of diagnostic testing has not been associated with reductions in disease‐related mortality but has led to increased overall healthcare costs and other unintended consequences (e.g., incidental findings requiring further workup, unnecessary exposure to ionizing radiation or potentially nephrotoxic contrast). Shared decision making (SDM) presents an opportunity for clinicians to discuss the benefits and harms associated with diagnostic testing with patients to more closely tailor testing to patient risk. This article introduces the challenges and opportunities associated with incorporating SDM into emergency care by summarizing the conclusions of the diagnostic testing group at the 2016 Academic Emergency Medicine Consensus Conference on SDM. Three primary domains emerged: 1) characteristics of a condition or test appropriate for SDM, 2) critical elements of and potential barriers to SDM discussions on diagnostic testing, and 3) financial aspects of SDM applied to diagnostic testing. The most critical research questions to improve engagement of patients in their acute care diagnostic decisions were determined by consensus.